Intriguing Relationships Between Cancer and Systemic Sclerosis: Role of the Immune System and Other Contributors - Maria, Alexandre Thibault Jacques; Partouche, Léo; Goulabchand, Radjiv; Rivière, Sophie; Rozier, Pauline; Bourgier, Céline; Le Quellec, Alain; Morel, Jacques; Noël, Danièle; Guilpain, Philippe (Frontiers in Immunology, 2019)
Systemic sclerosis (SSc) is an autoimmune connective tissue disorder, characterized by multisystem involvement, vasculopathy, and fibrosis. An increased risk of malignancy is observed in SSc (including breast and lung cancers), and in a subgroup of patients with specific autoantibodies (i.e., anti-RNA polymerase III and related autoantibodies), SSc could be a paraneoplastic syndrome and might be directly related to an immune response against cancer. Herein, we reviewed the literature, focusing on the most recent articles, and shed light onto the potential relationship between cancer and scleroderma regarding temporal and immunological dimensions.